Designing Assessmake21 for Self-Reflection in Maker Education: Insights from a Design Case - Mavri, Aekaterini; Ioannou, Andri; Kitsis, Andreas (My University, 2025)
In this design case we introduce Assessmake21, a digital self-assessment tool to foster self-reflection for learners’ 21st-century skills in K-12 formal and non-formal maker education. We report on the extraction of user requirements and corresponding UI features through a four-phase design process, led by a multidisciplinary team of 29 members from four European countries. Using a methodological UX process model and requirements taxonomy, the design team translated theory-driven and data-driven evidence - gathered through literature reviews, design thinking workshops, interviews, and expert feedback—into tool design specifications. Assessmake21 aims to promote scaffolded and sustained self-reflection through gamified features (level progression, content unlocking, rewards) and customizable learning design options (approach, duration), while integrating the educator’s role into the skills’ assessment process. This comprehensive end-to-end design case is a valuable resource for researchers and practitioners, offering a precedent for similar long-term, multi-stakeholder and multi-cultural incentives and advancing scholarship in learning experience design.
Keywords: EdTech (Educational Technology); UX; codesign; learning experience design; maker education; design case